French-language health services in Canada: The state of the law - Foucher, Pierre (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This analysis of the legal framework of the active offer of French language health care in Canada will examine its constitutional and legislative elements. The first part will explore the constitutional dimension, looking at aspects related to the Canadian Constitution and the Canadian Charter of Rights and Freedoms enshrined therein. In the second part, we will consider language laws at the federal level and in the provinces and territories. The study will show the asymmetrical nature of the legal model and the challenges it engenders. Key Words: legal framework, law, health care, Canadian Charter of Rights and Freedoms, Canadian Constitution.